Civilian Militarism, Democracy, and State Capacity in Venezuela and Colombia, 1998-2016 - Rodriguez Hernandez, Saul Mauricio (Université d'Ottawa | University of Ottawa, 2024)
How do elected leaders secure long-lasting political dominance of their factions, including transferring power to their successors? The existing literature has given limited attention to comprehending the strategies employed by presidents to secure lasting political influence, including the subsequent transition of power to close political allies upon the completion of their tenures. Notably, an important but consistently overshadowed pathway for achieving this goal is militarism. When integrated into political strategies, militarism can gradually erode democracy over time through a series of militaristic discourses, practices, and actions ostensibly aimed at enhancing deteriorated state capacity under presidents' political strategies. This dissertation explores the relationship between political and military power in Venezuela and Colombia from 1998 to 2016, and the emergence and consolidation of civilian militarism as a by-product of this relationship. Despite both countries being governed democratically, they succumbed to radical political strategies - "Bolivarianism" and "Democratic Security", respectively. Each gained immense popularity and had significant impacts domestically and internationally. The central argument of the dissertation revolves around the idea that militarism - and specifically civilian militarism - in Latin America is not a by-product of geopolitical competition, as suggested by the scholarship building on the work by Michael Mann and Charles Tilly; instead, it is a response to the pressure of economic changes wrought by neoliberalism and domestic circumstances aimed at enhancing state capacity to protect presidents' political strategies and goals. Building on Mann's scholarship, civilian militarism is defined as the promotion of militaristic values related to war and preparedness for war by civilian elected authorities (political power). These authorities advance political objectives by encouraging various militaristic actions, attitudes, and societal norms. By drawing upon Mann's theoretical framework on sources of social power (political and military) and supplementing it with original contributions, this dissertation demonstrates that civilian militarism is wielded as a tool to bolster state capacities in alignment with the political objectives of presidents. Military power is assimilated as a means of infrastructural and despotic power, ostensibly to enhance state capacities and elected leaders' political goals. Nevertheless, if left unchecked, this approach poses a long-term threat to democratic regimes and can potentially blur the boundaries between political and military power, paving the path toward authoritarianism. This dissertation makes a significant contribution to the understanding of the emergence and consolidation of civilian militarism within democratic contexts. It likewise contributes to the study of politics in Colombia and Venezuela, highlighting development that allowed elected leaders to retain political power, while also facilitating authoritarianism.
Keywords: militarism; state; democracy; democratic backsliding; civilian militarism; state capacity; Colombia; Venezuela; Michael Mann; constructivism; military